ANALISIS FAKTOR PENYEBAB CONTRACT CHANGE ORDER MENGGUNAKAN EXPLORATORY FACTOR ANALYSIS PADA PROYEK JALAN - Andika Aristya; Eva Rita; Zulherman Zulherman (Fakultas Teknik, Universitas Riau Kepulauan, 2026)
Changes in construction projects in the form of Contract Change Orders (CCOs) are unavoidable phenomena that often lead to cost overruns and project schedule delays. This study aims to identify the factors causing CCOs, determine the dominant factors contributing to CCO occurrences, and provide insights into CCO control implications in the Sultan Thaha Road improvement project in Sungai Penuh City. A quantitative research approach was employed, with data collected through questionnaires distributed to 35 respondents directly involved in the project implementation. Data analysis was conducted using descriptive analysis and exploratory factor analysis with the assistance of SPSS software. The results indicate that all research instruments are valid and reliable, and the data meet the requirements for factor analysis, as evidenced by KMO values greater than 0.5 and Bartlett’s Test significance values below 0.05. The factor analysis results reveal three main factors influencing CCOs: planning and site condition factors, execution and technical factors, and supervision and resource factors. Among these, the planning and site condition factor is identified as the dominant factor, contributing 66.312% to the occurrence of CCOs. These findings suggest that inadequate initial planning and discrepancies between actual site conditions and contract documents are the primary causes of work changes. This study is expected to serve as a reference for project owners, consultants, and contractors in improving project planning and control practices to minimize the occurrence of CCOs in road construction projects.